Associations between problematic internet use and substance misuse among US college students. (September 2022) - Qeadan, Fares; Egbert, Jamie; English, Kevin
Abstract: Problematic internet use (PIU) is more common in young adult populations than any other adult age group. Previous research has suggested that PIU is associated with higher rates of mental health disorders, psychological distress, and some substance misuse behaviors in college students. This study utilizes data from 417, 780 US college students to explore associations between PIU and a variety of substance use outcomes. Unadjusted and adjusted odds ratios were used to investigate associations between PIU and substance use disorder (SUD) diagnosis, misuse of cigarettes, e-cigarettes, alcohol, marijuana, cocaine/methamphetamine, sedatives, hallucinogens, opiates, inhalants, MDMA, other club drugs, prescription pain killers, prescription sedatives, and prescription stimulants. Among the 417, 780 US college students included in our analytic cohort, 123, 330 (29.52%) reported PIU. Students who demonstrated PIU had a significantly higher risk of substance misuse behaviors, including misuse of opiate, sedative, hallucinogen, club drugs, and inhalant, illicit use of prescription pain killers, and SUD diagnosis, than their peers who did not demonstrate patterns of PIU. These findings highlight the need to promote the physical, social, and emotional wellbeing of students more effectively by considering PIU in prevention and intervention efforts aimed to decrease the prevalence of addictive behaviors in US college settings. Highlights: Problematic internet use is associated with an increased risk of opiate misuse among US college students. Problematic internet use is associated with an increased risk of illicit prescription pain killer use. Students who exhibit problematic internet use are at increased risk for being diagnosed with substance use disorder. A commonly established definition of problematic internet use is needed to increase the comparability of research findings. Problematic internet use should be addressed in addictive behavior prevention and intervention efforts in college settings.